Pemberdayaan Usaha Minuman Sarang Burung Walet - Yanuar Fauzuddin; Hario Adji Pamungkas; Antoni Antoni; Andi Iswoyo; Hendrik Rizqiawan (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2021)
This activity aims to increase the capacity of partners in managing the swallow's nest beverage business. The increased capacity is awareness of food safety in the production process, ability in online marketing and the ability to calculate the selling price accurately. This capacity building is aimed at increasing business income. The methods used range from counseling, training, capital assistance to mentoring. Counseling and training were carried out classically by discussion and practice. Capital assistance is provided to help implement the results of outreach and training. Assistance is carried out to assist partners in dealing with difficulties in implementing the results of outreach and training. The partner in this activity is Mrs. Sri Wahyuni, who has a bird's nest drink business since 2019.